The detection of formaldehyde using microelectromechanical acoustic resonator with multiwalled carbon nanotubes-polyethyleneimine composite coating. (8th December 2017) - Wang, Jingjing; Zhan, Da; Wang, Ke; Hang, Weiwei
Abstract: A micro-scale gas sensor based on mass-sensitive film bulk acoustic resonator is demonstrated for the detection of trace formaldehyde at room temperature. The composites mixed with multiwalled carbon nanotubes and polyethyleneimine (MWNTs-PEI) were coated on the resonator surface as the sensitive layer to specifically absorb formaldehyde molecules using a facile spray process. The influence of spraying processes on the formaldehyde sensing properties were investigated. Different response behaviors were determined by both the chemical absorption between formaldehyde molecules and the amine functional groups on PEI and the increase of absorption surface came from the nanostructure. The combination of high frequency of the film bulk acoustic resonator (~4.3 GHz) and the specific absorbability of MWNTs-PEI composites provided a high sensitivity in the detections of trace formaldehyde. The obtained ultra-low limit of detection was as low as 60 ppb with linear response, quick response/recovery time, good reproducibility and selectivity. The proposed sensor shows potential as a portable and convenient gas-sensing system for monitoring the low-level concentration of indoor air pollution.